Urinary analysis of 8-oxoguanine, 8-oxoguanosine, fapy-guanine and 8-oxo-2′-deoxyguanosine by high-performance liquid chromatography–electrospray tandem mass spectrometry as a measure of oxidative stress - Malayappan, Bhaskar; Garrett, Timothy J.; Segal, Mark; Leeuwenburgh, Christiaan (Journal of Chromatography A, 2007)
A sensitive and specific assay aimed at measuring the oxidized nucleic acids, 8-oxoguanine (8-oxoGua), fapy-guanine (Fapy-Gua), 8-oxoguanosine (8-oxoGuo), 8-oxo-2′-deoxyguanosine (8-oxodG) has been developed by coupling reversed phase liquid chromatography (HPLC) with electrospray tandem mass spectrometry detection (MS/MS) and isotope dilution. The HPLC–MS/MS approach with multiple reaction monitoring (MRM) allowed for the sensitive determination of 8-oxoGua, Fapy-Gua, 8-oxoGuo, and 8-oxodG in human urine samples. There is no sample preparation needed except for the addition of buffer and 13C- and 15N-labeled internal standards to the urine prior to sample injection into the HPLC–MS/MS system. This method was tested in urine samples from non-smokers, smokers, non-smokers with chronic kidney disease (CKD) and smokers with CKD, to assess the level of oxidative damage to nucleic acids. Markers of both RNA and DNA damage were significantly increased in the smokers with and without CKD compared to their respective control subjects. These findings suggest that a highly specific and sensitive analytical method such as isotope dilution HPLC–MS/MS may represent a valuable tool for the measurement of oxidative stress in human subjects.